2019
DOI: 10.1097/aog.0000000000003521
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Midwifery and Obstetric Care in Low-Risk Hospital Births

Abstract: OBJECTIVE: To compare midwife and obstetrician labor practices and birth outcomes in women with low-risk pregnancies delivered in the hospital. METHODS: We conducted a retrospective cohort study of singleton births of 37 0/7–42 6/7 weeks of gestation at 11 hospitals between January 1, 2014, and December 31, 2018. Exclusions included intrapartum transfer from home-birth center, antepartum stillbirth, previous cesarean delivery, practitioner other than mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 15 publications
3
41
0
5
Order By: Relevance
“…75,76 Effective collaboration has been identified as critical to US obstetric/midwifery practice models with improved outcomes. 77,78 Key factors for successful collaboration were integration of care, mutual trust and respect, regulation for the full scope of midwifery practice, and interprofessional education. There is a growing maternity workforce crisis in the United States; over half of US counties do not have a maternity provider.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Effective collaboration has been identified as critical to US obstetric/midwifery practice models with improved outcomes. 77,78 Key factors for successful collaboration were integration of care, mutual trust and respect, regulation for the full scope of midwifery practice, and interprofessional education. There is a growing maternity workforce crisis in the United States; over half of US counties do not have a maternity provider.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that CNMs may have lower overall unplanned cesarean rates compared with obstetricians managing low‐risk pregnancies, but the rate of cesarean and the risks by provider type specifically for labor after cesarean are not known. We hypothesized that CNM management of low‐risk TOLAC patients increases vaginal delivery success without additional morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…13 Despite the small but potentially catastrophic risks of TOLAC, it remains cost-effective and provides improved long-term health outcomes compared with scheduled repeat cesarean. 20 Data suggest that CNMs may have lower overall unplanned cesarean rates compared with obstetricians managing low-risk pregnancies, [21][22][23] but the rate of cesarean and the risks by provider type specifically for labor after cesarean are not known. We hypothesized that CNM management of low-risk TOLAC patients increases vaginal delivery success without additional morbidity.…”
mentioning
confidence: 99%
“…11 More recent work has used statistical methods to control for a priori differences in the population of women served by midwives and the population served by physicians. 12 These techniques can adjust for variables that are known to independently influence an individual's risk for cesarean as long as those variables are present in the data, but they cannot control for variables that are not accounted for or are unknown, a limitation of all observational studies. Systematic reviews are designed to assess the full body of relevant published research in order to identify a consistent theme or effect.…”
mentioning
confidence: 99%
“…The independent effect of midwifery care on cesarean birth rates in settings where obstetric interventions such as neuraxial analgesia, intravenous medications, and cesarean are commonly employed has been difficult to parse. Some studies have found that midwifery care is associated with lower cesarean rates, whereas others have found that midwifery care is not associated with a change in cesarean rates . Given all studies that have compared the outcomes of individual women after receipt of midwifery or obstetric care are generally positive but potentially confounded by different types of bias, it is time to look at this issue differently.…”
mentioning
confidence: 99%